1992
DOI: 10.1021/bi00148a004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic conformations compared for IgE and IgG1 in solution and bound to receptors

Abstract: Dynamic conformations of two distinct immunoglobulin (Ig) isotypes, murine IgE and human IgG1, were examined with fluorescence resonance energy transfer measurements. The IgE mutant epsilon/C gamma 3* and the IgG1 mutant gamma/C gamma 3* each bind [5-(dimethylamino)naphthalen-1-yl]sulfonyl (DNS) in two identical antigen binding sites at the amino (N)-terminal ends of the Ig in the Fab segments. Eosin-DNS bound in these Fab sites served as the acceptor probe in these studies. Both Ig have a carboxy (C)-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
46
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 35 publications
8
46
0
Order By: Relevance
“…We note first that the derived composition of the complex does not depend on the accuracy with which the partial specific volumes are known-that is to say, on the carbohydrate content of the constituents-because the buoyant molecular weight, determined from the sedimentation equilibrium distribution, is the sum of the buoyant molecular weights of the constituent glycoproteins. The It has been suggested that IgE may be bent (26,27), and this distortion could occur, at least in part, within the CE2-CE3 linker. The consequences of this were investigated by using the extended model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note first that the derived composition of the complex does not depend on the accuracy with which the partial specific volumes are known-that is to say, on the carbohydrate content of the constituents-because the buoyant molecular weight, determined from the sedimentation equilibrium distribution, is the sum of the buoyant molecular weights of the constituent glycoproteins. The It has been suggested that IgE may be bent (26,27), and this distortion could occur, at least in part, within the CE2-CE3 linker. The consequences of this were investigated by using the extended model.…”
Section: Resultsmentioning
confidence: 99%
“…and S.J.P., unpublished results). In the absence of more detailed structural information, this distortion is generally represented as being evenly distributed between all the linker regions separating the immunoglobulin domains (1,26,27 The hydrodynamic evidence limits the range of possible models for the complex of IgE-Fc and sFcsRIa to those in which the domains of the IgE-Fc overlap with those of the sFceRla (Fig. 4 g-j), although two T-shaped models (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive energy transfer studies suggest that IgE is bent at the junction of its C⑀2 and C⑀3 domains (19 -23). Furthermore, the bent structure of IgE in solution appears to be similar in conformation to receptor-bound IgE (19,23). These data suggest that the binding site for Fc⑀RI could be on the convex surface of IgE and thus the concave surface would not be available for the binding of a second receptor.…”
mentioning
confidence: 98%
“…However, no direct evidence has been presented to confirm a conformational rearrangement upon binding. Furthermore, later energy transfer studies suggest that the bent conformation of IgE does not change significantly upon binding (19,23).…”
mentioning
confidence: 99%
“…This means that these small molecules have to present at least two epitopes for cross-linking the IgE, which could be difficult from a stereochemical point of view. Moreover, through the absence of a hinge region, IgE is rather rigid, and its flexibility is limited when bound to Fc⑀RI, where IgE is fixed in a bent shape (7,8). The cross-linking situation is even more stringent in the case of B lymphocyte activation, because each B cell expresses only one type of Ig with one epitope specificity.…”
mentioning
confidence: 99%